Van der Waals Heterostructures: Controllable Magnetic Proximity Effect and Charge Transfer in 2D Semiconductor and Double‐Layered Perovskite Manganese Oxide van der Waals Heterostructure (Adv. Mater. 50/2020). Issue 50 (15th December 2020) - Zhang, Yan; Shinokita, Keisuke; Watanabe, Kenji; Taniguchi, Takashi; Goto, Masato; Kan, Daisuke; Shimakawa, Yuichi; Moritomo, Yutaka; Nishihara, Taishi; Miyauchi, Yuhei; Matsuda, Kazunari
Abstract : Optically excited states in semiconductors are highly sensitive to the physical properties of the materials underneath. In article number 2003501, Kazunari Matsuda and co‐workers demonstrate modulation and control of the excitonic states (excitons and trions) in a novel van der Waals heterostructure of a monolayer semiconductor on the strongly correlated electron system of perovskite manganese oxide with a thin insulating layer, wherein manganese oxide transforms from a paramagnetic insulator to a ferromagnetic metal.